Marbury V. Madison to Present Day: Tracing the Evolution and Significance of Judicial Review - Bashir, Aiman; Khan, Yasir Rashid (Law and Policy Review, 2023)
The concept of judicial review signifies power vested in the superior judiciary by the judiciary itself where it can revisit the legislation. The ambit of the doctrine of judicial review stretches its boundary line to the decisions of administrative authorities as well. Marbury v. Madison was essentially seen as a vital case when it was decided since it laid down the foundation of the very power. It dynamically acquired quality and prominence, nonetheless, and is currently valued by people. It is considered to be a landmark case because it established the judicial organ as the co-equal part of the government. Many people consider judicial review as an essential part of the separation of powers. Its job as a foundation of judicial power holds a practically matchless spot of significance in judicial history. The judicial review was previously implicated in Bonham’s case. It was criticized by legal advisers, judges, and laymen as, according to them, allowing unelected judges to fix the legislation drawn up by the representative institution in a democratic country is hardly justified. The current study attempted to dig out Bonham’s case rationale alongside the arguments put forward in Marbury’s case where it emerged to be the powerful tool possessed by the judicial organ of the state.